READING COMPREHENSION PROBLEMS ENCOUNTED BY THE STUDENTS OF HIGHER EDUCATION - Anie Susany Soemantri (Jurnal Computech & Bisnis (e-Journal), 2015)
One of the ability to speak English is reading in addition to listening, speaking, and writing. By reading ability in college students will greatly assist in the understanding of the scientific text books that guide the learning process at the college. Scientific understanding of the text book is very important in the success of the student’s graduation he attended courses that will ultimately accelerate the student graduation. Then all the need for analysis of reading comprehension problems faced by students in the college. Keywords: Reading Comprehension, Students, Higher Education    Abstrak Salah satu kemampuan berbahasa inggris yaitu reading disamping listening, speaking, dan writing. Dengan kemampuan reading pada mahasiswa perguruan tinggi akan sangat membantu dalam melakukan pemahaman terhadap buku text ilmiah yang menjadi pedoman dalam proses belajar pada perguruan tinggi. Pemahaman terhadap text book ilmiah sangat penting dalam keberhasilan mahasiswa untuk kelulusan mata kulaih yang diikutinya yang pada akhirnya akan mempercepat kelulusan mahasiswa tersebut. Dengan demikain perlu adanya analisis terhadap masalah reading comprehension yang dihadapi mahasiswa pada perguruan tinggi. Kata Kunci: Reading Comprehension, Mahasiswa, Perguruan Tinggi